Investigation of SiO2-Al2O3 nanolaminates for protection of silver reflectors - Schwinde, S.; Schuermann, M.; Kaiser, N.; Tuennermann, A. (Applied Optics, 2017)
H2S and particles from the atmosphere can damage silver reflectors. These defects lead to scattering and a reduction of reflectivity. With regard to these risks, the suitability of sputtered SiO2, Al2O3, and SiO2-Al2O3 nanolaminates for the protection of Ag was analyzed. The optical properties, protection properties against H2S, solubility, film stress, and protection properties against particle-induced defect formation have been investigated. Especially in the case of particle-induced defects on protected Ag, differences between the protective coatings are considerable, and the nanolaminate layers have advantageous properties.
CRIS-Team Scopus Importer:2023-04-20